The US, NATO, and military burden-sharing - Forster, Peter Kent (Contemporary security studies., 2005)
This study establishes that the political, economic and military-technological changes that transform the international system also alter the way in which a state views its and others' responsibilities and burdens for responding to international crises. It assesses the distribution of the costs of raising and supporting arms of service, the risks of deploying them overseas and using them in combat or peace operations, and the extent to which members have a responsibility for maintaining international order in the context of three instances of multinational military intervention: the Multinatio.